A study on user engagement program in Malaysian academic library during COVID-19 / Fatimah Az Zahra binti Zainud-din and Roziya Abu - Zainud-din, Fatimah Az Zahra; Abu, Roziya (Faculty of Information Management, 2022)
User engagement is essential to ensure the organization can achieve their objective, especially in providing services to the users, such as the academic library, which provide information and services to students, lecturers, researchers, and others. However, COVID-19 has spread wildly and severed the established connection, which resulted in the interruption of information delivery. Thus, the academic library finds ways to reach its users and provide the required services despite the obstacles. In this period, exploring methods used by the library to engage with users is intriguing.